Relationship between muscular strength and sprints with changes of direction - Castillo-Rodriguez, A.; Fernández-Garcia, J. C.; Chinchilla-Minguet, J.; Carnero, E. A. (The Journal of Strength and Conditioning Research, 2012)
Sprints with changes of direction (COD) have been traditionally associated with performance in team sports. Jumping tests have been used as predictors of COD; however, there are not too many studies analyzing how dominance affects the best performance of the turn. The purpose of this study was to explore the relationship between tests pertaining to jumps (1 and 2 legs) and COD (right and left turns). Forty-two male students were selected at the Faculty of Physical Education (age: 20.1± 3.7 years; weight: 73.4 ± 8.4 kg; body mass index: 23.1 ± 2.6 kg/m; and fat mass: 17.1 ± 8.8%). All the subjects had right leg dominance. The COD tests were assessed using three 10-m sprint tests (90° right and left turns and 180° turn). Jumps were countermovement jumps (CMJs with 1 and 2 legs) and the drop jump (DJ). Pearson coefficient correlation and stepwise regression analyses were performed. Our results showed that both CMJs and DJs were associated with COD. The CMJ with the right leg had the best coefficient correlation with left COD time (r = -0.64; p < 0.01). Also, the CMJ was associated with COD180° time (r = -0.60; p < 0.01). After regression analysis, only right one-leg CMJ and CMJ were predictors of left COD time (adjusted R2 = 0.46; p < 0.01). The main finding of this study was that the CMJ, but not the DJ, was the best predictor of dominant side COD. Jumps are an important component of team sport training because they improve COD performance. However, coaches use several types of jumps during training; our results suggest that jumps similar to the CMJ should be useful tools to improve COD, which helps to specify better training prescription.